6(a-7)+10=4(a-7)

Simple and best practice solution for 6(a-7)+10=4(a-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(a-7)+10=4(a-7) equation:


Simplifying
6(a + -7) + 10 = 4(a + -7)

Reorder the terms:
6(-7 + a) + 10 = 4(a + -7)
(-7 * 6 + a * 6) + 10 = 4(a + -7)
(-42 + 6a) + 10 = 4(a + -7)

Reorder the terms:
-42 + 10 + 6a = 4(a + -7)

Combine like terms: -42 + 10 = -32
-32 + 6a = 4(a + -7)

Reorder the terms:
-32 + 6a = 4(-7 + a)
-32 + 6a = (-7 * 4 + a * 4)
-32 + 6a = (-28 + 4a)

Solving
-32 + 6a = -28 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
-32 + 6a + -4a = -28 + 4a + -4a

Combine like terms: 6a + -4a = 2a
-32 + 2a = -28 + 4a + -4a

Combine like terms: 4a + -4a = 0
-32 + 2a = -28 + 0
-32 + 2a = -28

Add '32' to each side of the equation.
-32 + 32 + 2a = -28 + 32

Combine like terms: -32 + 32 = 0
0 + 2a = -28 + 32
2a = -28 + 32

Combine like terms: -28 + 32 = 4
2a = 4

Divide each side by '2'.
a = 2

Simplifying
a = 2

See similar equations:

| 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t | | 4(x+6)-4=6(x+3)-6 | | 6y-5=7y | | 4x-6=x+49 | | 1.25a=1.22 | | 2x^2+89=-4 | | 1.25a=1.22222 | | 66w-37-23w=49 | | 52c-14-35c=133 | | 0.065(x+2000)=0.07x+0.04(1000) | | 5-(a+3)=2a+6-3a | | 7p+6p= | | 10x+6y=97.5 | | x-4=2(2x-5) | | 10x+3=7x+4 | | 7n-n+12= | | 2x=3x+29 | | 8y-3=5y-8 | | 0.6x-0.4(40+x)=0.3(40) | | 5+20m-2m=-13 | | 5(2+n)=3n*18 | | 0.1(60)=0.4(30+x)-0.7x | | 36=6v |

Equations solver categories